ANALISIS HADIS-HADIS TENTANG FADILAH SHALAT BERJAMAAH - Dame Siregar (Yurisprudentia: Jurnal Hukum Ekonomi, 2016)
Its Imam nicely its reading to Al-Qur’an at the same time reading its[his] [him/ it]. Its imam know minimum amount ofread sentence at  Shalat which ispracticing. My me', i'tidal, sujud and sit [among/between] two sujud follow Rasul Shalat, minimum of its size measure ofhim come near for the price of al-Fatihah suroh. Minimum is amount of sentence the read ismy me sign'. Reading reading of hadis, is obliged to be read by wearing science of tajwid. Study reading and way of Rasul Shalat before Shalat menagamalkan, non taught by moment of Shalat. Way of meeting bershaf, diametrical, adult in front of, men children, woman child and adult woman, if one men makmum hence its parallel position with Imam right side, if coming men again hence its position offirst dishaf stand up about with left foot ofImam with its right feet hence first makmum retreat parallel position with both second makmum. Way of real correct bershaf represent indicator perfection of berjamaah salat. Voice Imam ought to earn to be heard bymakmum clearly. Reading amen by maximal Imam ofhim can only be heard by people. Pray after used up Shalat by each slow or sir non ossifying to read each so that Mosque reecho. Recitate with sir or whisper only pertinent able to listen it. Practice existing qabliah Shalat  among 2 until 4 rokaat, follow the example of midday qabliah 2 or 4 rokaat, qoblq ' asar 2 or 4 rokaat, Magrib qabliah 2 magrib ba'da rokaat 2, isya ba,da' 4 and at dawn qabliah 2 rokaat. Qabliah Isya' and jumu'ah not yet been found. Taking care of jamaah don't grab. Imam agree makmum if is wrong. position of Makmum if 1 people stand up left side